COMMUNICATION PATTERNS OF DPC HPDKI PANGANDARAN IN PRERERVING THE PERFORMING ARTS OF GARUT SHEEP - Triyani, Ika ika; Bajari, Atwar; Samson, Samson (Jurnal Visi Komunikasi, 2025)
This research discusses the effectiveness of organizational communication patterns of the Pangandaran Regency Branch Board of the Indonesian Sheep and Goat Breeders Association (DPC HPDKI) in preserving the art of Garut Sheep agility. The preservation of this tradition is reflected in the consistency of organizing performances every month which is an important part of efforts to maintain local culture. DPC HPDKI plays an important role in disseminating information, coordinating activities, and maintaining the sustainability of the tradition through structured communication patterns. The purpose of this study is to identify the factors that form the HPDKI DPC organization, analyze the organizational communication patterns, and understand the flow of information dissemination in it. This research used a qualitative method with a case study approach. Data collection techniques were conducted through in-depth interviews and participatory observation of nine informants who are members of the HPDKI DPC. Organizational information theory was used as the basis for data analysis. The results showed that organizational communication patterns are informal, familial, and flexible. WhatsApp is the main media for internal coordination due to its ease and speed of access, while social media is used for public promotion purposes. Information is conveyed openly through various communication channels available. This research shows that effective organizational communication not only contributes to the preservation of local culture, but also has an impact on improving the welfare of farmers and the stability of livestock prices.